A Subjective Understanding of the Concept of Human Suffering with the Frame of Reference of Theodor. H. Adorno and His Critical Theory Arching to a Dialectical Turn: Exploring the Role of the Body in Adorno's Critical Theory and Its Potential Contribution to Feminist Philosophy of Disability (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Critical theorist Theodor Adorno is rarely considered as a philosopher of the body. The body which leaks, desires, rages and lusts is seemingly disjointed from the dry and dense writings that often characterize Adorno's work. As bleak as this description of Adorno's writings may be, however, the body is both central to his critique of modernity and the site of hope and desire against the total domination and suffering that capitalism imposes. This paper highlights some of the ways in which feminist philosophy of disability and disability studies, more generally, would benefit by thinking in constellation with Adorno's negative dialectic to interrogate the ways in which meanings get made about bodies and, furthermore, use the margins of difference, in relation with others, to challenge what Adorno calls the wrong state of things. I argue that the transfigured crip to come is central to this fight against the wrong state of things.